PENGARUH INTENSITAS KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH TERHADAP KINERJA GURU - Istiqlalya, Tazkira; Achmad Taufik Ismail; Ilham Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the principal’s interpersonal communication intensity on teacher performance. The research employs a quantitative approach with a correlational design. The population consists of all teachers at SMPIT Al-Imaroh Cikarang Barat, totaling 30 respondents, using a saturated sampling technique. Data were collected through questionnaires and documentation. The indicators of interpersonal communication intensity include frequency, duration, regularity, attention, breadth, and depth of messages, while teacher performance is measured through task achievement, work quality, punctuality, compliance with standards, and professional responsibility. The results show that both interpersonal communication intensity and teacher performance are in the moderate category. Correlation analysis indicates a strong and significant relationship between the variables, with a correlation coefficient of 0.751. Furthermore, simple linear regression analysis reveals a positive and significant effect, with a contribution of 56.5%. These findings indicate that higher intensity of interpersonal communication by the principal can improve teacher performance. Therefore, more intensive, open, and continuous communication is essential to enhance teachers’ understanding, motivation, and overall professional performance.